ANALISIS FAKTOR YANG MEMPENGARUHI TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Putri, Vidiyanna Rizal (Jurnal Manajemen Dayasaing, 2019)
The aim of this study is to determine and analyze Â the effect of income tax variables, bonus mechanisms, incentive tunneling to transfer pricing. The sample selection using purposive sampling method and the sample of this research are 23 manufacturing companies listed in Indonesian Stock Exchange (IDX). The data are obtained from secondary data of annual report of basic and manufacture companies listed in Indonesia Stock Exchange in 2012-2016. The analysis technique used in this research is binary logistic regression analysis. The hypothesis in this study is based on previous research and various other supporting theories. The results of this study indicate that the income tax is significant and significant to the transfer pricing, incentive Tunneling influential and significant to transfer pricing, while the bonus mechanism does not affect the transfer pricing.